Dissipation of Monocrotophos From Mung Bean Under Arid Conditions - Singh, M P (Annals of Arid Zone, 2016)
Residues following application of 0.04 and 0.06 per cent monocrotophos on mung bean [Vigna radiala (L) wilezek] crop were estimated for two consecutive seasons at Jodhpur through bioassay method. The insecticide was found persisting upto three weeks in leaves, while in pods, it lasted for two weeks. Waiting periods of 8 and 7 days were estimated for foliage for higher and lower concentrations, respectively. On pods, the waiting periods were found to he 7 days for higher concentration and 6 days for the lower one. No residues were detected in the grains at harvest.